Highly Modulated In-Fiber Mach–Zehnder Interferometer Based on an Ultracompact Leaky-Guided Liquid Core - Lee, Cheng-Ling; Zhuo, Wei-Rong; Liu, Tai-Kai (Sensors (Basel, Switzerland), 2022)
We proposed a novel sensor based on an ultracompact leaky-guided liquid core fiber Mach–Zehnder interferometer (LLCFMZI) for high modulation of an interference spectrum. The sensor structure is based on a micro-sized hollow-core fiber (HCF) splicing a tilt end face single-mode fiber (SMF) to create a miniature oblique gap for the effective access of different liquids. The liquid core with a relatively lower refractive index (RI) than the cladding can achieve a leaky-mode optical waveguide (LMOW) mechanism, and its volume is only approximately 7.85 pL. In addition, the utilized micro-length HCF can reduce the energy loss of core in the LMOW to obtain an acceptable extinction ratio (>30 dB) with high temperature (T) sensitivity in the interference spectra. Experimental results show that the interference spectra can be highly modulated within the wide measurement range of 1250–1650 nm with a steadily linear response for thermal effect. The measured temperature sensitivities (T-sensitivities) of various liquids of DI water, ethanol, and Cargille-liquid (nD = 1.305) are 0.8869, 4.4754, and 4.8229 nm/°C, and the corresponding measured thermal optics coefficient (TOC) are −4.16 × 10−5, −2.11 × 10−4, and −3.6 × 10−4 °C−1, respectively. Measurement results demonstrate that the used liquids with a higher TOC can obtain better T-sensitivity modulation. The highest experimental sensitivity of the liquid-core filled with Cargille-liquid (nD = 1.40) is up to +13.87 nm/°C with a corresponding TOC of −4.07 × 10−4 °C−1. Furthermore, the experimental and theoretical values are in good agreement according to FSR the measuring scheme that investigates the effectiveness of the proposed LLCFMZI.